A - Santrock, John W. (McGraw-Hill Education, 2014)
Informed and driven by research. At McGraw-Hill, we have spent thousands of hours with you and your students, working to understand the key needs and concerns you face in the Human Development course. The most common topics raised include managing the vast amount of content inherent to a Lifespan course and ensuring the dependability of the assigned material – is it current and accurate? The result of this research is John Santrock's A Topical Approach to Lifespan Development, 7e. Santrock ensures students complete and understand the assigned material in a number of ways: Santrock's hallmark Learning Goals pedagogy provides a comprehensive roadmap to the text material, clearly pointing out the core concepts fundamental to students' learning and performance